A surge of late-occurring meiotic double-strand breaks rescues synapsis abnormalities in spermatocytes of mice with hypomorphic expression of SPO11 - Faieta, Monica (Chromosoma, 2015)
Meiosis is the biological process that, after a cycle of DNA replication, halves the cellular chromosome complement, leading to the formation of haploid gametes. Haploidization is achieved via two successive rounds of chromosome segregation, meiosis I and II. In mammals, during prophase of meiosis I, homologous chromosomes align and synapse through a recombination-mediated mechanism initiated by the introduction of DNA double-strand breaks (DSBs) by the SPO11 protein. In male mice, if SPO11 expression and DSB number are reduced below heterozygosity levels, chromosome synapsis is delayed, chromosome tangles form at pachynema, and defective cells are eliminated by apoptosis at epithelial stage IV at a spermatogenesis-specific endpoint. Whether DSB levels produced in Spo11(+/−) spermatocytes represent, or approximate, the threshold level required to guarantee successful homologous chromosome pairing is unknown. Using a mouse model that expresses Spo11 from a bacterial artificial chromosome, within a Spo11(−/−) background, we demonstrate that when SPO11 expression is reduced and DSBs at zygonema are decreased (approximately 40 % below wild-type level), meiotic chromosome pairing is normal. Conversely, DMC1 foci number is increased at pachynema, suggesting that under these experimental conditions, DSBs are likely made with delayed kinetics at zygonema. In addition, we provide evidences that when zygotene-like cells receive enough DSBs before chromosome tangles develop, chromosome synapsis can be completed in most cells, preventing their apoptotic elimination. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00412-015-0544-7) contains supplementary material, which is available to authorized users.